A preliminary evaluation of unified protocol in anxiety disorders in India: a multiple baseline study protocol - B., Arunya; Sudhir, Paulomi Matam; Sundar Arumugham, Shyam (International Journal of Clinical Trials, 2023)
Background: Anxiety disorders are highly prevalent with high rates of comorbidity. Single disease protocols have been the predominant choice of psychological treatment, however, there has been an increasing focus on transdiagnostic, shared mechanisms. Unified protocol is an emotion-focused CBT that addresses core vulnerabilities by training individuals in adaptive emotion regulation skills. UP has gained research attention in the management of emotional disorders with its modular approach. A challenge in psychotherapy research has been to understand the mechanisms of interventions and their effect on symptoms. Thus single-case experimental design has the potential to address some of the key questions. We present a research protocol that aims to examine the effectiveness of the unified protocol, using the SCED. Methods: A single-case experimental design, with multiple baseline assessments, will be employed, with random allocation to 2- or 3-week baselines. Patients with a primary diagnosis of anxiety disorder, consenting to baseline assessments, and stabilized at least for 4 weeks of medication will be recruited. Assessments will be carried out at baseline, post, and three months, in addition to weekly assessments on the primary outcome measure, anxiety by an independent blind rater. Secondary outcomes include intolerance to uncertainty, neuroticism, emotion regulation, and anxiety sensitivity. Conclusions: The findings of this study would contribute to the empirical status of transdiagnostic interventions in symptom reduction and in addressing shared mechanisms, enhancing its clinical relevance for co-morbid disorders. Trial Registration: The study has been registered in clinical trials registry of India, No. CTRI/2021/01/030803; 28 January 2021.